Vitamin D and Menopause - admin; Megha Sharma; Sanjay Kalra (Journal of the Pakistan Medical Association, 2024)
Menopause is the transition period in female life cycle. Resultant hormonal changes lead to adverse health effects. Women may seek treatment due to significant impairment in quality of life. Vitamin D deficiency is a globally prevalent problem. Vitamin D deficiency in menopausal women may aggravate the adverse health risks associated with menopause. In this article, the authors discuss endocrinology and clinical features of menopause, Vitamin D and its links with menopause, and the potential role of Vitamin D supplementation to combat detrimental multi-organ system effects of menopause. KEYWORDS: Vitamin D, menopause, Vitamin D supplementation